Student Response Rate and Its Impact on Quantitative Evaluation of Faculty Teaching - Mingchu Neal Luo (The Advocate, 2020)
Student evaluations of teaching (SET) generate essential information for university administrators and faculty in assessing instruction quality. Lower response rates in student surveys have remained an important technical issue hurting the credibility of SET. This study examined the student response rate and its impact on the results of student quantitative evaluations of faculty teaching in a college of education. It analyzed the quantitative data of course evaluations collected by using the IDEA (Individual Development and Educational Assessment, 2016) survey at a teaching-orientated Midwest state university. Results indicate that 1) the average student response rate of all these courses is 63.6%, 2) there is no significant relationship between the enrollment size of the classes and response rate of SET for these classes, and 3) response rates to the course evaluation survey significantly associates with the overall mean scores of students’ ratings, showing that classes evaluated by students with lower response rates tend to have lower evaluation mean scores. Implications for instruction evaluation policy and faculty practices for valid use of SET and increasing response rate are discussed.
Keywords: IDEA; student evaluation; response rate; faculty teaching